Continuous Renal Replacement Therapy for Acute Renal Failure in Patients with Cancer: A Well-Tolerated Adjunct Treatment - Fischler, Rebecca; Meert, Anne-Pascale; Sculier, Jean-Paul; Berghmans, Thierry (Frontiers in Medicine, 2016)
Abstract Introduction – Acute renal failure (ARF) has a poor prognosis in patients with cancer requiring intensive care unit (ICU) admission. Our aim is finding prognostic factors for hospital mortality in patients with cancer with ARF requiring renal replacement therapy (RRT). Methods – In this retrospective study, all patients with cancer with ARF treated with continuous venovenous filtration (CVVHDF) in the ICU of the Institut Jules Bordet, between January 1st 2003 and December 31st 2012, were included in the study. Results – 103 patients are assessed: men/women 69/34, median age 62 years, solid/haematologic tumours 68/35, median SAPS II 56. Mortality rate was 63%. Seven patients required chronic renal dialysis. After multivariate analysis, two variables were statistically associated with hospital mortality : more than one organ failure (including kidney) (OR 5.918 ; 95% CI 2.184 – 16.038 ; p<0,001) and low albumin level (OR 3.341; 95% CI 1.229 – 9.077; p=0,02). Only minor complications related to CVVHDF have been documented. Conclusions – Despite the poor prognosis associated with ARF, CVVHDF is an effective and tolerable renal replacement technique in patients with cancer admitted to the ICU. Multiple organ failure and hypoalbuminemia, two independent prognostic factors for hospital mortality have to be considered when deciding for introducing RRT.